The effect of gut-training and feeding-challenge on markers of gastrointestinal status in response to endurance exercise: a systematic literature review - Martinez, I. G.; Mika, A. S.; Biesiekierski, J. R.; Costa, R. J. S. (Sports Medicine, 2023)
Background: Nutrition during exercise is vital in sustaining prolonged activity and enhancing athletic performance; however, exercise-induced gastrointestinal syndrome (EIGS) and exercise-associated gastrointestinal symptoms (Ex-GIS) are common issues among endurance athletes. Despite this, there has been no systematic assessment of existing trials that examine the impact of repetitive exposure of the gastrointestinal tract to nutrients before and/or during exercise on gastrointestinal integrity, function, and/or symptoms. Objective: This systematic literature review aimed to identify and synthesize research that has investigated the impact of `gut-training` or `feeding-challenge` before and/or during exercise on markers of gastrointestinal integrity, function, and symptoms. Methods: Five databases (Ovid MEDLINE, EMBASE, CINAHL Plus, Web of Science Core Collection, and SPORTDiscus) were searched for literature that focused on gut-training or feeding-challenge before and/or during exercise that included EIGS and Ex-GIS variables. Quality assessment was conducted in duplicate and independently using the Cochrane Collaboration`s risk-of-bias (RoB 2) tool. Results: Overall, 304 studies were identified, and eight studies were included after screening. Gut-training or feeding-challenge interventions included provision of carbohydrates only (n = 7) in various forms (e.g., gels or liquid solutions) during cycling or running, or carbohydrate with protein (n = 1) during intermittent exercise, over a varied duration (4-28 days). Gut discomfort decreased by an average of 47% and 26% with a 2-week repetitive carbohydrate feeding protocol (n = 2) and through repeated fluid ingestion over five trials (n = 1), respectively. Repetitive carbohydrate feeding during exercise for 2 weeks resulted in the reduction of carbohydrate malabsorption by 45-54% (n = 2), but also led to no significant change (n = 1). The effect of gut-training and feeding-challenges on the incidence and severity of Ex-GIS were assessed using different tools (n = 6). Significant improvements in total, upper, and lower gastrointestinal symptoms were observed (n = 2), as well as unclear results (n = 4). No significant changes in gastric emptying rate (n = 2), or markers of intestinal injury and permeability were found (n = 3). Inconclusive results were found in studies that investigated plasma inflammatory cytokine concentration in response to exercise with increased carbohydrate feeding (n = 2). Conclusions: Overall, gut-training or feeding-challenge around exercise may provide advantages in reducing gut discomfort, and potentially improve carbohydrate malabsorption and Ex-GIS, which may have exercise performance implications.